Walls without boundaries: re-imagining the spaces of orphan-care in South Africa - Thomas, Samantha (My University, 2019)
South Africa has a large number of orphaned and vulnerable children (OVC’s) with little hope for a brighter future. Many of these children are often robbed of their childhood, forced to grow up and fend for themselves; this often resulting in living on the street or being the sole provider for their household. Without guidance from those who are older and wiser, the likelihood is high that neglected, vulnerable children will grow up in negative environments which lead to lives that are characterized by poor decisions and unstable lifestyles. By prioritizing care for these orphaned and vulnerable children through creating a safe and secure environment for them to grow and learn, the lives of the younger generation can be shaped and changed. Different types of care-systems exist in South Africa for OVC’s, but the stereotype of many of these structures has a negative stigma attached to it. The various building typologies of the current care of vulnerable children will be explored to understand the benefits and shortfalls of the respective organisations. The typical family-unit will also be investigated, and principles will be extracted on the relationship between care and development of children. By analysing both orphan-care as well as typical families, the principles gained from both can be combined in a housing scheme that mitigates such a negative stigma. The design of the study will be based on extensive research in the form of direct observations , personal interviews with professionals in the field, document reviews and analysis of precedent studies. This research will aid in gaining an understanding the issues surrounding OVC’s, and therefore will help inform the architectural intervention that will result from this project. In culmination of the research, this project aims to explore how architecture can improve the well-being of orphaned and vulnerable children, specifically in Johannesburg, South Africa. By interrogating different methods of building design, the intent of the housing scheme which will be supplemented by a healthcare, community, and skills development centres which will encourage community integration while still providing a place of protection and growth for these children.
Keywords: Orphans-South Africa; Land tenure-South Africa